2007
DOI: 10.1007/s11258-007-9318-5
|View full text |Cite
|
Sign up to set email alerts
|

Land use history, hurricane disturbance, and the fate of introduced species in a subtropical wet forest in Puerto Rico

Abstract: Tropical forests are suffering from increasing intensities and frequency of disturbances. As a result, non-native species accidentally introduced or intentionally planted for farming, plantations, and ornamental purposes may spread and potentially invade undisturbed native forest. It is not known if these introduced species will become invasive, as a result of recurrent natural disturbances such as hurricanes. Using data from three censuses (spanning 15 years) of a 16-ha subtropical wet forest plot, we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 36 publications
2
42
0
1
Order By: Relevance
“…Similar typhoon effects have been seen in Tahiti (Meyer 1994) and Florida (Horvitz et al 1998). However, other reviews have found that vegetation on some islands subject to frequent typhoons may regenerate rapidly following wind disturbances with little change in species composition (Brokaw & Walker 1991, Franklin et al 2004, Thompson et al 2007. Our data were not adequate for evaluating the role of typhoon frequency on island ecosystems.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Similar typhoon effects have been seen in Tahiti (Meyer 1994) and Florida (Horvitz et al 1998). However, other reviews have found that vegetation on some islands subject to frequent typhoons may regenerate rapidly following wind disturbances with little change in species composition (Brokaw & Walker 1991, Franklin et al 2004, Thompson et al 2007. Our data were not adequate for evaluating the role of typhoon frequency on island ecosystems.…”
Section: Discussionsupporting
confidence: 46%
“…While the objective was to restore Hawaii's watersheds, the project also provided opportunity for the establishment and spread of invasive exotic species into native forests at an unprecedented scale. Historic afforestation projects have contributed also to the exotic flora of Australia (Lonsdale 1994), but not apparently to that of Hong Kong (Corlett 1999) or Puerto Rico (Thompson et al 2007) where assessments found that few exotic species used for reforestation or plantations in the past had naturalized or posed a threat to native forest.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of the influence of land-use history on secondary forests communities in Puerto Rico are limited to samples selected along land-use gradients within small landscapes that encompass only one climatic zone and substrate type (García-Montiel and Scatena, 1994;Rivera and Aide, 1998;Pascarella et al, 2000;Thompson et al, 2002Thompson et al, , 2007Molina and Lugo, 2006). These studies find that past land use has an overriding impact on secondary forest species composition.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were collected 1 month before (pre-hurricane), 2 months after, 1 year after, and 2 years after the pass of Hurricane Wilma. Different letters indicate significant (P \ 0.05) differences among sampling dates within each seral stage (means ± SE, N = 6) the recovery of forest canopy after a large, infrequent disturbance is heavily influenced by prior site history (Foster et al 1999;Uriate et al 2004;Chazdon 2003;Thompson et al 2007). We found early-and mid-seral stages to be more resilient to a hurricane disturbance, whereas the taller, late-seral forest (Table 1), with more biomass to lose, appeared more vulnerable.…”
Section: Discussionmentioning
confidence: 99%